Penegakan Hukum Terhadap Pelanggaran Kode Etik Yang Dilakukan Oleh Oknum Polisi - Yefri Arraniri; Subekti .; Ernu Widodo (JOURNAL OF SHARIA ECONOMICS, 2022)
Law enforcement against law enforcement officers is a primary prerequisite for the realization of a democratic state based on the rule of law. This article aims to analyze in-depth the law enforcement mechanism against ethical code violations and criminal acts committed by members of the Indonesian National Police (Polri) and to identify the obstacles that affect its effectiveness. This research uses a normative juridical method with a statutory, conceptual, and comparative approach. The results of the study indicate that law enforcement against police officers is carried out through two main channels: criminal justice and the Indonesian National Police Professional Code of Ethics Commission hearings. Although an adequate normative framework is in place, its implementation still faces structural, cultural, and institutional obstacles, such as conflicts of interest, weak internal oversight, and low public participation. Therefore, strengthening the oversight system, transparency of the law enforcement process, and reform of the internal legal culture of the Indonesian National Police are necessary.